Comparison of Endoscopic Sliced Cartilage versus Temporalis Fascia Grafting For Tympanic Membrane Perforations - Dr Alok Yadav; Dr Ritesh Surana; Dr Neeti Sahay; Dr Samanvaya Soni, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Aim: The aim of the present study was to compare endoscopic sliced cartilage versus temporalis fascia grafting for tympanic membrane perforations. Methods: A prospective comparative study was conducted involving 100 patients with central tympanic membrane perforations. Patients were divided into two groups: one receiving endoscopically placed sliced tragal cartilage grafts, and the other receiving temporalis fascia grafts. Surgeries were performed under endoscopic guidance. Postoperative follow-up was carried out for three to six months. Results: The cartilage graft group demonstrated a higher graft uptake success rate of 92%, compared to 85% in the temporalis fascia group. This difference was statistically significant (p < 0.05). Audiological outcomes were similar between both groups, with an average ABG closure of 12–15 dB. While both grafts provided effective hearing restoration, cartilage exhibited superior durability and resistance to retraction, especially in patients with Eustachian tube dysfunction, anterior perforations, or recurrent ear infections. Conclusion: Endoscopic sliced cartilage tympanoplasty offers superior anatomical success compared to temporalis fascia, with comparable functional (audiological) outcomes. It is especially beneficial in high-risk cases, such as large, anterior, or recurrent perforations, and in patients with poor middle ear ventilation. While temporalis fascia remains a reliable option in straightforward cases, cartilage should be the preferred graft in complex tympanoplasties. Tailoring the graft material to the patient’s middle ear condition and perforation characteristics is crucial for optimizing surgical success.